Konsep Mental Health Pendekatan Terapi Islam - Musripah, Musripah (Journal of Sufism and Psychotherapy, 2024)
Humans are unique creatures. With their uniqueness, humans are complicated and mysterious creatures. Humans ethically uphold goodness, nobility, altruism, or sacrifice, and consider them to be noble values. Mental health (mental hygiene) is a science that includes a system of principles, regulations and procedures to improve spiritual health. A mentally healthy person is a person who spiritually or in his heart always feels calm, safe and at ease. In the millennial era, it is often found in both agencies and institutions that morals, morals, ethics are starting to erode, and another thing is becoming a world problem, namely the disease outbreak called the corona virus. There are some who use it as a source of income by hoarding illegal masks and selling them at prices that have skyrocketed far from normal prices, and on the one hand they are empathetic by protecting the health of individuals and the surrounding environment. If there is restlessness, restlessness and anxiety, it can be categorized as mental health problems. Based on these problems, the author is interested in writing and analyzing how to apply the concept of mental health, sickness and health, how to approach religion. This research uses a qualitative research library research approach. The data used uses primary and secondary data, the analysis used uses content analysis.